Orthographic standardisation in early Modern English: London, Wellcome Library, MS 3009. - Criado-Peña, Miriam (Studia Neophilologica, 2022)
Early Modern English is regarded as the key period in the establishment of the written standard of the language. The present study contributes to the discussion on the standardisation processes of the English spelling in the period. It assesses the level of orthographic standardisation of London, Wellcome Library, MS 3009 (ff. 17 r–90 r), a 17th-century recipe book. The orthographic variables considered fall into four criteria: complementary distribution of graphemes, vowel length, word separation and hyphenation and line-final word division. For the purpose, a semi-diplomatic transcription of MS Wellcome 3009 has been carried out, which allows for both a quantitative and a qualitative approach to the study of orthographic standardisation of the text under consideration.